Therapeutic Reference Ranges for Psychotropic Drugs: A Protocol for Systematic Reviews - Hart, Xenia M.; Eichentopf, Luzie; Lense, Xenija; Riemer, Thomas; Wesner, Katja; Hiemke, Christoph; Gründer, Gerhard (Frontiers in Psychiatry, 2021)
Background: For many psychotropic drugs, monitoring of drug concentrations in the blood (Therapeutic Drug Monitoring; TDM) has been proven useful to individualize treatments and optimize drug effects. Clinicians hereby compare individual drug concentrations to population-based reference ranges for a titration of prescribed doses. Thus, established reference ranges are pre-requisite for TDM. For psychotropic drugs, guideline-based ranges are mostly expert recommendations derived from a conglomerate of cohort and cross-sectional studies. A systematic approach for identifying therapeutic reference ranges has not been published yet. This paper describes how to search, evaluate and grade the available literature and validate published therapeutic reference ranges for psychotropic drugs. Methods/Results: Following PRISMA guidelines, relevant databases have to be systematically searched using search terms for the specific psychotropic drug, blood concentrations, drug monitoring, positron emission tomography (PET) and single photon emission computed tomography (SPECT). The search should be restricted to humans, and diagnoses should be pre-specified. Therapeutic references ranges will not only base upon studies that report blood concentrations in relation to clinical effects, but will also include implications from neuroimaging studies on target engagement. Furthermore, studies reporting concentrations in representative patient populations are used to support identified ranges. Each range will be assigned a level of underlying evidence according to a systematic grading system. Discussion: Following this protocol allows a comprehensive overview of TDM literature that supports a certain reference range for a psychotropic drug. The assigned level of evidence reflects the validity of a reported range rather than experts' opinions.